PERAN PEREMPUAN DALAM LINGKUNGAN ALAM PADA KOMIK LUH AYU MANIK MAS: KAJIAN EKOFEMINISME: Kajian Ekofeminisme - Dewi, Ni Made Candra; Sulibra, I Ketut Ngurah; Sutika, Nyoman Duana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research discusses seven series in the comic entitled Luh Ayu Manik Mas, namely Komik Luh Ayu Manik Mas Series 1 (Tresna Ring Alas), Komik Luh Ayu Manik Mas Series 2 (Ngae Mobile Library), Komik Luh Ayu Manik Mas Series 3 (Environmental Hero ), Comic Luh Ayu Manik Mas Series 4 (Fighting Plastic Luu), Comic Luh Ayu Manik Mas Series 5 (Local Mamula Woh-Wohan), Comic Luh Ayu Manik Mas Series 6 (Ngalahang Legu Poleng), and Comic Luh Ayu Manik Mas Series 7 (Ngrejek Village Virus Monster). This research aims to determine the structure and explain the role of women in the Luh Ayu Manik Mas Comic Series one to seven. This research uses structural theory, ecofeminist theory and feminist theory. This research is a type of qualitative descriptive research. The methods and techniques used in this research are the listening method with reading techniques and note-taking techniques. Next, data analysis uses qualitative methods assisted by analytical descriptive techniques. The stage of presenting the results of data analysis using a formal presentation method assisted by deductive techniques. The narrative structure that builds the story from the comic is incident, plot, character, setting, theme and message. The plot/plot uses a forward or progressive plot. The theme used is women's struggle to save the environment. One of the messages to be conveyed is to always preserve the environment. Furthermore, the role of women in the comic, namely Komik Luh Ayu Manik Mas, is the movement to care for the environment, the movement to preserve the environment, the movement to save the environment with the supernatural power of Luh Ayu Manik Mas, and the movement to keep the